A sensitive liquid chromatography method for analysis of propofol in small volumes of neonatal blood. (3rd October 2019) - Qi, Bing; Nicolaï, Johan; Smits, Anne; De Vocht, Tom; Deferm, Neel; Van Brantegem, Pieter; Allegaert, Karel; Annaert, Pieter
Abstract: What is known and objective: Sampling volumes of blood from neonates is necessarily limited. However, most of the published propofol analysis assays require a relatively large blood sample volume (typically ≥0.5 mL). Therefore, the aim of the present study was to develop and validate a sensitive method requiring a smaller sample volume (0.2 mL) to fulfill clinically relevant research requirements. Methods: Following simple protein precipitation and centrifugation, the supernatant was injected into the HPLC‐fluorescence system and separated with a reverse phase column. Propofol and the internal standard (thymol) were detected and quantified using fluorescence at excitation and emission wavelengths of 270 nm and 310 nm, respectively. The method was validated with reference to the Food and Drug Administration (FDA) guidance for industry. Accuracy (CV, %) and precision (RSD, %) were evaluated at three quality control concentration levels (0.05, 0.5 and 5 µg/mL). Results and discussion: Calibration curves were linear in the range of 0.005‐20 µg/mL. Intra‐ and interday accuracy (−4.4%‐13.6%) and precision (0.2%‐5.8%) for propofol were below 15%. The calculated LOD (limit of detection) and LLOQ (lower limit of quantification) were 0.0021 µg/mL and 0.0069 µg/mL, respectively. Propofol samples were stable for 4 months at −20°C after the sample preparation. This method was applied for analyzing blood samples from 41 neonates that received propofol, as part of a dose‐finding study. The measured median (range) concentration was 0.14 (0.03‐1.11) µg/mL, which was in the range of the calibration curve. The calculated median (range) propofol half‐life of the gamma elimination phase was 10.4 (4.7‐26.7) hours. What is new and conclusion: A minimal volume (0.2 mL) of blood from neonates is required for the determination of propofol with this method. The method can be used to support the quantification of propofol drug concentrations for pharmacokinetic studies in the neonatal population. Abstract : With the developed LC‐UV method, a minimal volume (0.2 mL) of neonatal blood is required to quantitatively determine propofol concentrations. The method will support pharmacokinetic studies with propofol in neonates.